Characterization of ionic liquid pretreated plant cell wall for improved enzymatic digestibility. (February 2018) - Raj, Tirath; Gaur, Ruchi; Lamba, Bhawna Yadav; Singh, Nitu; Gupta, Ravi P.; Kumar, Ravindra; Puri, Suresh K.; Ramakumar, S.S.V.
Graphical abstract: Highlights: Five ILs were employed for deconstruction of plant cell wall. Biomass was characterized by spectroscopy and surface morphology. [C2 mim][OAc] is more pronounced in all ILs to release high sugar. Higher pore size and surface area results in better glucose yield. TCI and LOI have a negative correlation with glucose yield. Abstract: An insight into the properties of cell wall of mustard stalk (MS) pretreated by five ionic liquids (ILs) revealed ILs interaction with cellulose, hemicellulose and lignin components. Differential Scanning Calorimetry (DSC) showed increased pore size coupled with increased population of pores evoked by certain ILs in better facilitating enzymatic accessibility. Interestingly, all the five ILs predominantly increased the propensity of two pore sizes formation; 19 and 198 nm, but remarkable difference in the pore volumes of pretreated MS suggested the supremacy of [OAc] − based ILs, resulting in higher glucose yields. Cellulose I to II transition in pretreated MS was supported by the reduced total crystallinity index (TCI), lateral order index (LOI) values. Strong inverse correlation existed between the said parameters and residual acetyl content with enzymatic hydrolysis (R 2  > 0.8). An inverse relationship between hydrogen bond basicity, LOI and TCI suggested it to be a good indicator of IL pretreatment efficiency.